Three-year crop rotation acted as a net carbon source and grazed grassland as a net sink in Argentine Pampas, revealing different management controls - Marconato, Ulises Mariano (2026)
Large efforts are devoted to quantifying the carbon impacts from changes in land use related to agricultural activities, but comparatively less attention is being paid to net carbon exchange in ongoing crop and cattle raising systems, especially in South America, where long-term studies are scarce. Using Eddy Covariance, we quantified carbon fluxes of a cropland (three-year rotation) and a nearby grazed grassland with rotational grazing in a mixed agricultural region of the Pampas in Argentina (MAP=1022 mm; MAT=16.1°C). We used classification trees to analyze the relationship between fluxes, management practices and environmental variables. Between 2018 and 2021, with average climatic conditions, net ecosystem exchange (NEE) was −5.06 ± 0.21 t C ha⁻¹ and −7.39 ± 0.09 t C ha⁻¹ for the grazed grassland and cropland, respectively. However, when carbon exports were included, the grazed grassland showed a net biome productivity (NBP) of −4.06 ± 0.41 t C ha⁻¹ (net sink), while the cropland showed a NBP of +2.03 ± 0.56 t C ha⁻¹ (net source). About 70% of the carbon fixed by crops was exported at harvest (9.4 ± 0.47 t C ha⁻¹), leaving insufficient carbon to offset losses during fallow periods, while meat-carbon exports (0.2 ± 0.04 t C ha⁻¹) from the grazed grassland reached 4% of fixed carbon. Management dominated carbon balance in croplands, while in grasslands, temperature and livestock presence were more influential. Management shaped carbon flux magnitude and direction in crops and carbon flux pathways in grasslands. Food production implies a balance between carbon exported and carbon retained in the soil, resulting in a trade-off between the ecosystem services of food provision and carbon sequestration. Our results suggest that a spatial arrangement could be implemented to compensate cropland emissions with carbon capture by almost permanent grasslands while sustaining food production, avoiding the carbon losses caused by land-use shifts in rotations aim at temporal compensation.